Distribution and Progression of Inflammatory Chorioretinal Lesions Related to Multifocal Choroiditis and Their Correlations with Clinical Outcomes at 24 Months. (17th February 2022) - Erba, Stefano; Cozzi, Mariano; Xhepa, Alba; Cereda, Matteo; Staurenghi, Giovanni; Invernizzi, Alessandro
ABSTRACT: Purpose: To analyze distribution and progression of multifocal choroiditis (MFC) inflammatory lesions and their correlations with clinical outcomes at 24 months. Methods: Distribution and progression of inflammatory lesions were evaluated in eyes with MFC using a semi-automatic approach based on fundus autofluorescence. Twenty-four-months clinical outcomes were correlated with baseline features. Results: Twenty-five eyes from 20 patients were enrolled. Visual acuity (VA) significantly improved from baseline to 24 months. Chorioretinal lesions spared the fovea in most eyes. The area of inflammatory lesions at 24 months significantly increased. Final number and area of lesions were significantly influenced by baseline features. Inflammatory lesions enlarged over time regardless of MFC recurrences. New lesion and MFC relapses did not affect final outcomes. Conclusions: Final VA correlated with baseline VA. Scars resulting from MFC lesions enlarged overtime even when the disease was under control. New lesions and MFC relapses did not affect final outcomes.